Extended-focused Ultrasonography for Children with High-energy Trauma - Özlem Tolu Kendir; Hayri Levent Yılmaz; Tuğçe Çelik; İlker Ünal; Sinem Sarı Gökay; Ahmet Kağan Özkaya (Journal of Pediatric Research, 2019)

(untitled)
Aim:Ultrasonography (USG) is an important tool used in the diagnosis of critical patients. The present study was carried out in order to detect intra-peritoneal free liquid in cases with high-energy trauma by using “extended-focused trauma (E-FAST) USG” and to determine the diagnostic power and benefits of this method.Materials and Methods:The medical records of pediatric cases with high-energy trauma were examined retrospectively. The results of computed tomography (CT) and radiologist-operated abdominal (Rad) USG and the demographic data of patients were compared with the results obtained from E-FAST-USG performed by a pediatric emergency specialist. Chi-square test was used to compare the categorical measurements among the groups.Results:One hundred and sixty patients were observed during the study period. When E-FAST-USG was compared to Rad-USG, the accuracy rate of E-FAST-USG was found to be 97.5%, sensitivity to be 90.9%, and specificity to be 98%. Forty-one of the patients were examined using CT. The sensitivity of Rad-USG was found to be 64.6% and specificity to be 93.3%, whereas the sensitivity of FAST-USG was found to be 81.8% and specificity to be 93.3%.Conclusion:FAST-USG can be used in pediatric trauma cases at high sensitivity-specificity levels, and the radiation exposure of CT, which is a major consideration during childhood, can be reduced.